Saccharin and aspartame excite rat retinal neurons - Yang, Jaeyoung; Myers, Jason; Slaughter, Malcolm M. (Frontiers in Ophthalmology, 2023)
Retinal sensitivity to a variety of artificial sweeteners was tested by monitoring changes in internal free calcium in isolated retinal neurons using Fluo3. Several ligands, including aspartame and saccharin elevated internal free calcium. The effects of these ligands were mediated by both ligand-gated membrane channels and G-protein coupled receptors. We explored the receptors responsible for this phenomenon. Surprisingly, mRNA for subunits of the sweet taste receptor dimer (T1R2 and T1R3) were found in retina. Interestingly, knockdown of T1R2 reduced the response to saccharin but not aspartame. But TRPV1 channel antagonists suppressed the responses to aspartame. The results indicate that artificial sweeteners can increase internal free calcium in the retinal neurons through multiple pathways. Furthermore, aspartame reduced the b-wave, but not the a-wave, of the electroretinogram, indicating disruption of communication between photoreceptors and second order neurons.